Correlation between Pre-Operative 25-Hydroxyvitamin D Levels and Poor Prognostic Factors for Papillary Thyroid Cancer. Issue 5 (4th May 2022) - Abuduwaili, Munire; Xing, Zhichao; Xia, Baoying; Fei, Yuan; Zhu, Jingqiang; Su, Anping
Abstract: Purpose: To evaluate the relationship between pre-operative 25-hydroxyvitamin D (25 (OH) D) levels and poor prognostic factors for papillary thyroid cancer (PTC). Methods: A total of 1161 patients diagnosed with PTC were analyzed retrospectively. The patients were categorized .based on their pre-operative 25 (OH) D levels into three groups: the severe vitamin D deficiency (VDD) group (25 (OH) D < 10 ng/mL), moderate VDD group (20 ng/mL > 25 (OH) D ≥ 10 ng/mL), and control group (25(OH)D ≥ 20 ng/mL) Differences in the demographic and clinicopathological characteristics among the three groups were analyzed. Linear and logistic regression analyses were also performed to determine the effect of 25 (OH) D levels on the established poor prognostic factors for PTC. Results: We observed a negative correlation between 25 (OH) D levels and tumor size (r = −0.067, P = 0.049). Severe VDD and moderate VDD were independently associated with lymph node metastasis and distant metastasis diagnosed during surgery ( P = 0.00, odds ratio (OR) = 4.11; P = 0.00, OR = 3.33, respectively). After adjusting parameters such as sex, age, body mass index, and thyroid-stimulating hormone (TSH) levels, severe VDD and moderate VDD were found to be closely associated with advanced cancer stage (stage III or IV) ( P = 0.018, OR = 3.02; P = 0.041, OR = 3.60, respectively). Additionally, a significant correlation ( P = 0.007) was observed between the pre-operative 25 (OH) D and TSH levels. Conclusion: 25 (OH) D levels were significantly associated with certain poor prognostic factors for PTC, including larger tumor diameter and the occurrence of lymph node metastasis. More prospective studies are needed to evaluate whether the assessment and supplementation of vitamin D contributes to the pre-operative management of patients with PTC.